Microencapsulação de gordura de coco com soro de leite para aplicação em ração de suínos - Migliavacca, Marina (2019)
The increased demand for higher value-added products is affected by global market trends. The implantation of new technologies as an alternative to the use of the generated by-products, which can present problems to the environment, is of economic, technological and environmental importance for the industries. Considering the large volume of whey derived from cheese production, which has high nutritional value and the environmental pollution associated with its inadequate destination, industries are looking for viable alternatives for their use. As well as whey, oils and fats are important ingredients due to their nutritional properties, as an energy source, and incorporation into a variety of food products, both in human and animal food. Coconut fat is used in pig feed as an excellent source of energy, especially in the post weaning period, considered critical in terms of nutrition. Due to susceptibility to oxidation, coconut fat should be protected to avoid transformations that negatively affect its nutritional and sensory properties. The use of technologies such as microencapsulation followed by Spray dryer drying gives the food industry tools for the development of products with appropriate sensorial characteristics, without loss of aromatic compounds and avoids the chemical instability created by air, light, high temperatures and humidity. these are the factors responsible for the degradation and evaporation of labile ingredients. In this way, the objective of the work was to develop a process to microencapsulate the coconut fat by drying in Spray dryer, being used as the main wall material the whey, with addition of maltodextrin and gum arabic. Coconut fat had a high content of saturated fatty acids. Homogenization of the coconut fat with the encapsulating agents at a pressure of 200 bar provided the breaking of the lactose crystals and the fat globules, resulting in a homogenous sample. The best proportion of active agent:encapsulant was 1: 3 m / m, drying had low moisture content (<4%), minimal loss of product in the process. The microparticles presented high lactose content (75.84%), particle size less than 200 μm, water solubility of 49% and encapsulation efficiency of 67%, with the addition of maltodextrin, gum arabic and concentrated fat in powder, and these results are satisfactory because the final product will be added to animal feed on a dry basis and it will be stored protected from the external environment. The developed product resembles the commercial whey fat product, the encapsulating agents were able to protect the coconut fat, presenting high thermal stability (> 140 ° C) resulting in a safe, quality and final protected product.